Inactivity‐mediated molecular adaptations: Insights from a preclinical model of physical activity reduction - Alice Meyer; Nicole Kim; Melissa Nguyen; Monica Misch; Kevin Marmo; Jacob Dowd; Christian Will; Milica Janosevic; Erin J. Stephenson (Physiological Reports)
Abstract Insufficient physical activity is associated with increased relative risk of cardiometabolic disease and is an independent risk factor for mortality. Experimentally reducing physical activity rapidly induces insulin resistance, impairs glucose handling, and drives metabolic inflexibility. These adaptations manifest during the early stages of physical inactivity, even when energy balance is maintained, suggesting that inactivity‐mediated metabolic reprogramming is an early event that precedes changes in body composition. To identify mechanisms that promote metabolic adaptations associated with physical inactivity, we developed a mouse model of physical activity reduction that permits the study of inactivity in animals prior to the onset of overt changes in body composition. Adult mice were randomized into three groups: an inactive control group (standard rodent housing), an active control group (treadmill running 5 d/week for 6‐weeks), and an activity reduction group (treadmill running for 4‐weeks, followed by 2‐weeks of inactivity). Transcriptional profiling of gastrocnemius muscle identified seven transcripts uniquely altered by physical activity reduction compared to the inactive and active control groups. Most identified transcripts had reported functions linked to bioenergetic adaptation. Future studies will provide deeper characterization of the function(s) of each the identified transcripts while also determining how inactivity affects transcriptional regulation in other tissues.